The Use of mobile apps to support students’ mental health - Safitri, Nafilla Afania Afania (Maliki Interdisciplinary Journal, 2026)
Mental health among college students is an increasingly serious issue at both global and national levels. Students are vulnerable to psychological disorders such as stress, anxiety, and depression due to academic pressure and social demands. In the digital era, mobile applications have emerged as an accessible alternative solution to support mental health. This article aims to examine the use of mobile applications in supporting college students’ mental health through a literature review of 12 scientific articles published between 2021 and 2025. The results show that mobile applications are effective in reducing levels of stress, anxiety, and depression among students. The most studied types include meditation apps, mood trackers, online counseling platforms, and mental health screening tools. However, challenges such as stigma, privacy concerns, infrastructure limitations, and lack of local cultural contextualization remain barriers to optimal use. On the other hand, the large number of smartphone users in Indonesia presents a significant opportunity for developing more relevant and inclusive mental health applications. Collaboration between technology developers, psychologists, educational institutions, and the government is essential to create a comprehensive digital mental health ecosystem for Indonesian college students.